Bone Morphogenetic Protein-8B Levels at Birth and in the First Year of Life: Relation to Metabolic-Endocrine Variables and Brown Adipose Tissue Activity - Garcia-Beltran, Cristina; Villarroya, Joan; Plou, Cristina; Gavaldà-Navarro, Aleix; Casano, Paula; Cereijo, Rubén; de Zegher, Francis; López-Bermejo, Abel; Ibáñez, Lourdes; Villarroya, Francesc (Frontiers in Pediatrics, 2022)
Objective: Bone morphogenetic protein-8B (BMP8B) is an adipokine produced by brown adipose tissue (BAT) contributing to thermoregulation and metabolic homeostasis in rodent models. In humans, BAT activity is particularly relevant in newborns and young infants. We assessed BMP8B levels and their relationship with BAT activity and endocrine-metabolic parameters in young infants to ascertain its potentiality as biomarker in early life. Methods and Materials: BMP8B concentrations were assessed longitudinally by ELISA in a cohort of 27 girls and 23 boys at birth, and at age 4 and 12 months, together with adiposity parameters (DXA), and circulating endocrine-metabolic variables. BAT activity was measured by infrared thermography. BMP8B gene expression (qRT-PCR) was determined in BAT, white fat, and liver samples from neonatal necropsies, and in placenta and cord blood. Results: BMP8B levels were high at birth, particularly in boys (P=0.04 vs girls), declined progressively, and remained well above those in healthy adults and pregnant women at age one year (P<0.05 and P<0.001, respectively). Neonatal BMP8B transcript levels were higher in BAT than in white fat, liver and cord blood. Circulating BMP8B levels during the first year of life marginally correlated with bone mineral density and gains in lean mass. Conclusion: BMP8B levels are high at birth and decline progressively over the first year of life remaining above adult levels. Although changes in BMP8B concentrations overall reflect those in BAT activity during development, BMP8B levels are unlikely to be useful to predict individual variations in endocrine-metabolic status and BAT activity in healthy young infants.